2015
DOI: 10.1096/fj.15-272906
|View full text |Cite
|
Sign up to set email alerts
|

New aminopeptidase from “microbial dark matter” archaeon

Abstract: Marine sediments host a large population of diverse, heterotrophic, uncultured microorganisms with unknown physiologies that control carbon flow through organic matter decomposition. Recently, single-cell genomics uncovered new key players in these processes, such as the miscellaneous crenarchaeotal group. These widespread archaea encode putative intra- and extracellular proteases for the degradation of detrital proteins present in sediments. Here, we show that one of these enzymes is a self-compartmentalizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…The organoheterotrophic physiology of Bathyarchaeota was further supported through analyses of bathyarchaeotal genomes by single-cell genome and metagenome analyses, and genes encoding enzymes for the degradation, transport, and utilization of detrital proteins, aromatic compounds, and plant-derived carbohydrates were identified (2,11,14). Peptidase activity in the sediments was measured, and the gene of an extracellular peptidase from Bathyarchaeota was expressed in vitro and characterized, supporting the inferred capacity of Bathyarchaeota to degrade proteins (11,15). Meanwhile, stable-isotope probing experiments indicated that members of two subgroups assimilated several organic substrates, including acetate, glycine, urea, lipids, and complex mixtures of organic growth substrates, while showing no significant incorporation of carbon from proteins (16).…”
mentioning
confidence: 80%
“…The organoheterotrophic physiology of Bathyarchaeota was further supported through analyses of bathyarchaeotal genomes by single-cell genome and metagenome analyses, and genes encoding enzymes for the degradation, transport, and utilization of detrital proteins, aromatic compounds, and plant-derived carbohydrates were identified (2,11,14). Peptidase activity in the sediments was measured, and the gene of an extracellular peptidase from Bathyarchaeota was expressed in vitro and characterized, supporting the inferred capacity of Bathyarchaeota to degrade proteins (11,15). Meanwhile, stable-isotope probing experiments indicated that members of two subgroups assimilated several organic substrates, including acetate, glycine, urea, lipids, and complex mixtures of organic growth substrates, while showing no significant incorporation of carbon from proteins (16).…”
mentioning
confidence: 80%
“…Recent studies from marine and terrestrial subsurface environments has identified a variety of extracellular enzymes adapted to degrade detrital sedimentary organic matter (Michalska et al, 2015;Steen et al, 2019). Interestingly, the Salmeal sample (CGB7) contained a high fraction of unique unassigned Archaea (OTU8) as well as high abundance of uncultivated Acetothermia (OTU6).…”
Section: Discussionmentioning
confidence: 99%
“…Metagenome-assembled genomes have further revealed that diverse, heterotrophic microorganisms, with unknown physiologies, control the carbon flow in marine and hydrothermal deep-sea sediments via organic matter decomposition (Lloyd et al, 2013;Dombrowski et al, 2017). Hence, such microorganisms represent a great resource for finding new enzymes for biomedical, biotechnological, and industrial applications (Michalska et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Tryptophan synthase has become a prototype system to study the peculiarities of allostery and substrate channeling (Hilario et al, 2016;Niks et al, 2013;Rhee et al, 1996;Rowlett et al, 1998;Spyrakis et al, 2006). TrpA is also one of the model proteins that have been used to investigate protein-folding mechanisms (Wu & Matthews, 2002;Bilsel et al, 1999;Yang et al, 2007;Vadrevu et al, 2008;Wu et al, 2007;Michalska et al, 2015). The sparsity of biochemical/structural investigations of other orthologs possibly stems from challenges in obtaining high-quality TrpAB samples and also from interest being focused on very detailed mechanistic aspects rather than on species-specific variations.…”
Section: Figurementioning
confidence: 99%